PENERAPAN MEDIA PEMBELAJARAN E-FLASHCARD BERBASIS PERTANYAAN DENGAN SETTING THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN - Egianina Karina Br Tarigan; Putu Budi Adnyana; I Made Oka Riawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Biology learning on the human digestive system requires deep conceptual understanding, yet the cognitive engagement of eleventh-grade students at SMA Negeri 1 Kubutambahan remains low due to the limited variation of learning media used. This study aimed to determine the profile of learning outcome improvement, the difference in learning outcomes, and the effect size of applying question-based E-Flashcard learning media with a Think Pair Share (TPS) setting on students' learning outcomes on the human digestive system. This study used a quantitative approach with a quasi-experimental Nonequivalent Control Group Design. The sample consisted of 58 eleventh-grade science students selected through cluster random assignment, with class XI.3 as the experimental group (n=29) and class XI.4 as the control group (n=29). Data were collected using an essay test that had been tested for content validity (Gregory coefficient = 1.00), item validity (r-count 0.856– 0.930), and reliability (Cronbach's Alpha = 0.973). Data were analyzed using N-Gain and Analysis of Covariance (ANCOVA). The results showed that the mean N-Gain of the experimental class was 0.86 (high category), higher than the control class at 0.53 (moderate category). The ANCOVA test showed a significant difference in learning outcomes between the two classes (Sig. <0.001), with an adjusted mean of 92.711 for the experimental class and 69.289 for the control class. The effect size (Partial Eta Squared) of 0.804 was categorized as a large effect. It is concluded that question-based E-Flashcard learning media with a TPS setting is effective and has a large influence in improving students' cognitive learning outcomes on the human digestive system.